Bimbingan Keagamaan melalui Metode Khataman Kitab dalam Meningkatkan Kecerdasaan Spiritual - Nurhalizah, Nurhalizah; Arifin, Isep Zaenal; Saepulrohim, Asep (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This study aims to determine the initial conditions, processes and results of religious guidance through the method of khataman kitab in improving spiritual intelligence in the aspect of fathonah in students at Al-Faqih Dua Islamic Boarding School in Bandung. This research uses qualitative with the theory of khatman kitab method, spiritual intelligence of santri. The results showed that 1) the implementation of learning using the active knowledge sharing method ran smoothly rather than learning using the lecture method. 2) Students' critical thinking skills using the active knowledge sharing method are at the good category level, rather than using the lecture method. 3) Students' learning interests using active knowledge sharing method and lecture method are at very high and high criteria. 4) Comparison of learning results using both methods shows that the active knowledge sharing method is better in improving students' critical thinking skills and learning interest.